Grappling with the Complexity of Behavioral Processes in Human Psychological Suffering: Some Potential Insights from Relational Frame Theory - Harte, Colin; Barnes-Holmes, Dermot; de Rose, Julio C.; Perez, William F.; de Almeida, João H. [UNESP] (Springer Nature, 2023)
Relational frame theory (RFT) has historically been considered the basic explanatory science behind acceptance and commitment therapy (ACT). However, some have argued that there has been an increasing separation between the two in recent years. The primary aim of the current article is to explore the extent to which RFT concepts, particularly those that have been proposed recently in the context of “up-dating” the theory, may be used to build stronger links between basic and applied behavior analyses in which there is a shared language of relatively precise technical terms. As an example of this strategy, we outline RFT process-based experimental and conceptual analyses of the impact of one of the most widely used sets of interventions employed in the ACT literature, defusion. In addition, we suggest a potential experimental methodology for analyzing the basic behavioral processes involved. Overall, the current article should be seen as part of a broader research agenda that aims to explore how RFT may be used to provide a functional-analytic abstractive treatment of the behavioral processes involved in human psychological suffering.
Keywords: Acceptance and commitment therapy; Behavioral processes; Defusion; Psychological suffering; Relational frame theory